1995
DOI: 10.1111/j.1469-8749.1995.tb12045.x
|View full text |Cite
|
Sign up to set email alerts
|

The Life‐expectancy of Persons With Cerebral Palsy

Abstract: SUMMARY Survival rates for persons with cerebral palsy were calculated using information front a population‐based registry which has been collecting data since 1952. The 30‐year survival rate approximates 87 per cent. Adverse factors affecting survival are the type of cerebral palsy (spastic quadriplegia having the worst prognosis), epilepsy and severe or profound menial retardation. The length of time over which the data were collected precludes estimating survival time beyond 30 years. RÉSUMÉ Espérame de vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 4 publications
8
64
0
1
Order By: Relevance
“…They found that approximately 85% of children with severe four-limb cerebral palsy survived to 15 years of age, consistent with other studies (Hutton et al, 1994;Crichton et al, 1995;. The authors concluded that 15% of children with severe cerebral palsy died in childhood, suggesting that children with bilateral spastic cerebral palsy involving all four limbs are at a higher risk of mortality before they reach adolescence.…”
Section: The Prognosis Of Cerebral Palsysupporting
confidence: 80%
“…They found that approximately 85% of children with severe four-limb cerebral palsy survived to 15 years of age, consistent with other studies (Hutton et al, 1994;Crichton et al, 1995;. The authors concluded that 15% of children with severe cerebral palsy died in childhood, suggesting that children with bilateral spastic cerebral palsy involving all four limbs are at a higher risk of mortality before they reach adolescence.…”
Section: The Prognosis Of Cerebral Palsysupporting
confidence: 80%
“…Some of these variables, such as ambulatory and cognitive ability, which were not found to be significant predictors for survival, are heavily influenced by the very small numbers of ambulatory children and the very few individuals with high level cognitive function in our study group. Based on previous studies (Evans et al 1990;Crichton et al 1995;Eyman et al 1990Eyman et al , 1993Hutton et al 1994Hutton et al , 2000Plioplys et al 1998;Strauss et al 1998), large populations that include more high-functioning individuals demonstrate these as significant factors. However, few of these less involved patients develop severe scoliosis.…”
Section: Resultsmentioning
confidence: 99%
“…Crichton et al (1995) analyzed the data from the CP registry in British Columbia, Canada, and reported a mean 30-year survival rate of at least 87%, varying from 95% in patients with hemiplegia or monoplegia to 83.5% in those with quadriplegia having the worst prognosis. The most significant determinants for reduced life expectancy in pediatric patients with CP are the coexistence of other significant disorders such as respiratory malfunction, epilepsy, feeding disorders (particularly in patients requiring gastrostomy or nasogastric tube feedings), the degree of neurological involvement, the presence of severe cognitive abnormality, and the level of ambulatory disability (Evans et al 1990;Eyman et al 1990Eyman et al , 1993Hutton et al 1994Hutton et al , 2000Crichton et al 1995;Anderson 1996;Plioplys et al 1998;Strauss et al 1998). Respiratory disease, especially pulmonary infection, seems to be the predominant cause of death, specifically among individuals with mental retardation (Tarjan et al 1968, Chaney et al 1979, Eyman et al 1990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os níveis de sobrevida para pacientes com PC têm sido calculados usando informações de registros de dados da população colhidos desde 1952 20 . Aproximadamente 87% das pessoas com PC sobrevivem até os 30 anos 21 e quase 85% dos que passam dos 20 anos sobrevivem até os 50 anos 22 .…”
Section: Prognóstico Da Pc Expectativa De Vidaunclassified